T Helper Cell Subsets and Their Functions in Common Bottlenose Dolphins (Tursiops truncatus) - De Guise, Sylvain; Levin, Milton; Jasperse, Lindsay; Risatti, Guillermo; Wells, Randall S. (Frontiers in Immunology, 2019)
Considerable efforts have been made to better understand the immune system of bottlenose dolphins in view of the common environmental challenges they encounter, such as exposure to polychlorinated biphenyls, oil spills or harmful algal bloom biotoxins. However, little is known about the identity and functionality of the Th1, Th2 and Treg T helper cell subsets in bottlenose dolphins. The present study aimed at validating assays and reagents to identify T helper cell subsets and their functions in a subset of dolphins from Sarasota Bay, Florida, USA, which have been long studied and often used as a reference population. A population of CD4+ FOXP3+ lymphocytes was identified representing an average <1% of blood lymphocyte population, which is in the range observed in for Treg cells in other species. The use of porcine reagents to measure TGFß, one of the key Treg cytokines, was further validated using the relatively high-throughput and highly standardized Luminex technology. The proportion of circulating Treg cells was not correlated with the serum concentrations of the Treg effector cytokines TGFß and IL-10, nor could it significantly contribute to predicting the variability of T lymphocyte proliferation, suggesting that not all dolphin circulating Treg cells are functional and active. However, stimulation of dolphin lymphocytes with TGFß and IL-2 increased the expression of the gene for TGFß and IL-10, and stimulation with IL-12 and IFNγ induced a robust increase in the expression of the gene for IFNγ, suggesting the potential for polarization and differentiation of dolphin T helper cells towards a Treg and Th1 response, respectively. The lack of an increase in the expression of the genes for the Th2 cytokines IL-4 and IL-13 upon stimulation with IL-4 may be due to the requirement for IL-2 for a Th2 polarization as described in mice. However, regression analysis and PCA suggested the potential ability of both the Th1 and Th2 response to be triggered upon acute inflammatory signals. These results may be useful in better understanding the mechanisms by which the dolphin immune system is affected upon exposure to environmental challenges and how it responds to pathogen challenges.